2010
DOI: 10.1002/hep.23624
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-28B Genetic Variants and Hepatitis Virus Infection by Different Viral Genotypes

Abstract: Genetic host factors may modify the course of the hepatitis C virus (HCV) infection. Very recently, a genome-wide scan that reported association of the IL28B locus with response to treatment in HCV infection was published. The aim of the current study was to investigate the relationship of this locus with outcome of HCV infection in a cohort constituted by a total of 731 Spanish individuals. From these, 284 were subjects with persistent infection, 69 were individuals who naturally cleared the virus, and 378 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
147
5
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(186 citation statements)
references
References 18 publications
30
147
5
4
Order By: Relevance
“…Similar data were reported from Spain by Montes-Cano et al 41 Tillman et al evaluated the role of the rs12979860 polymorphism in a cohort of German women who had received anti-D immunoglobulin contaminated with HCV genotype 1b three decades earlier from 1978 to 1979. 43 They found that spontaneous viral clearance was seen in 6% of T/T homozygotes, 24% of C/T heterozygotes, and 64% of C/C homozygotes.…”
Section: −12supporting
confidence: 62%
“…Similar data were reported from Spain by Montes-Cano et al 41 Tillman et al evaluated the role of the rs12979860 polymorphism in a cohort of German women who had received anti-D immunoglobulin contaminated with HCV genotype 1b three decades earlier from 1978 to 1979. 43 They found that spontaneous viral clearance was seen in 6% of T/T homozygotes, 24% of C/T heterozygotes, and 64% of C/C homozygotes.…”
Section: −12supporting
confidence: 62%
“…Meanwhile, 80% of patients who carry 2 copies of this advantageous variant clear the virus during IFN therapy and remain virus-free with a sustained viral response. This mutation is more common in Caucasian and Asian populations, whereas it is only found in 40-50% of sub-Saharan Africans who are known to be more resistant to combination therapy (Thomas et al, 2009;Montes-Cano et al, 2010;Tillmann et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Further evidence that rs12979860 and rs8099917 SNPs of the IL28B locus are associated with spontaneous clearance is provided by cohorts of Swiss, Spanish, Australian and German patients with acute HCV infection followed during the course of hepatitis. [7][8][9][10] Few data are available on the association between IL28B SNPs and severity of liver fibrosis or presence of cirrhosis, and, in any case, these remain controversial. [11][12][13] We studied the relations of host genetic patterns of the IL28B locus (rs12979860 and rs8099917 SNPs), viral factors (positivity of serum HCV-RNA and HCV genotype), and liver iron overload, with spontaneous HCV clearance, severity of liver fibrosis, and SVR to interferon in a large, ethnically homogeneous cohort of thalassemia major (TM) patients with HCV infection.…”
Section: Il28b Polymorphisms Influence Stage Of Fibrosis and Spontanementioning
confidence: 99%
“…Analysis of the IL28B genotype effect according to a recessive model was pre-planned, based on previous results. [2][3][4][5][6][7][8][9][10] Multiple logistic regression models were used to assess the relationships among genetic (rs12979860 and rs8099917 SNPs), demographics (age and gender), and histological (classes of liver fibrosis and the liver iron concentration) features and spontaneous clearance of HCV, evidence of severe liver fibrosis, and response to antiviral therapy. Variables with a threshold value of P=0.1 at univariate analysis were included in the model, and variables with a threshold value of P≤0.05 were considered significant in the final model.…”
Section: Statisticsmentioning
confidence: 99%